2005
DOI: 10.1007/s10653-005-7857-z
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Cadmium and Zinc in Paddy Soils and Elevated Levels of Cadmium in Rice Grain Downstream of a Zinc Mineralized Area in Thailand: Implications for Public Health

Abstract: Prolonged consumption of rice containing elevated cadmium (Cd) levels is a significant health issue particularly in subsistence communities that are dependent on rice produced on-farm. This situation is further exacerbated in areas of known non-ferrous mineralization adjacent to rice-based agricultural systems where the opportunity for contamination of rice and its eventual entry into the food chain is high. In the current study, an assessment of the degree of soil Cd and Zn contamination and associated rice g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
194
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(201 citation statements)
references
References 30 publications
4
194
3
Order By: Relevance
“…In general, total metal levels for Cd, Cu, Pb, and Zn in individual samples were highly correlated with correlation coefficients ranging from 0.6 to 0.9 (data not shown). Similar trends of metal levels in soil in paddy fields have been observed by Simmons et al (2005), and the distance within a paddy field to the main inlet of irrigation water is crucial in relation to the metal levels observed in soil. These examples indicate that soil monitoring programs have to consider the heterogeneous nature of metal distribution between and within paddy fields in order to be able to accurately assess human health and ecosystem risks related to metals in soil in industrialized areas like those in the western plains of Taiwan.…”
Section: Soil Properties Across the Paddy Fieldssupporting
confidence: 79%
“…In general, total metal levels for Cd, Cu, Pb, and Zn in individual samples were highly correlated with correlation coefficients ranging from 0.6 to 0.9 (data not shown). Similar trends of metal levels in soil in paddy fields have been observed by Simmons et al (2005), and the distance within a paddy field to the main inlet of irrigation water is crucial in relation to the metal levels observed in soil. These examples indicate that soil monitoring programs have to consider the heterogeneous nature of metal distribution between and within paddy fields in order to be able to accurately assess human health and ecosystem risks related to metals in soil in industrialized areas like those in the western plains of Taiwan.…”
Section: Soil Properties Across the Paddy Fieldssupporting
confidence: 79%
“…This map was created using Geographic Information Systems software (Arc GIS version 10.2,ESRI Inc.,Redlands,Calif) In addition, China's rough rice imported from other countries accounted for 1.9 % of the national total yield in 2014, 99 % of which was from Thailand (NBS 2015;Shi 2015). The International Water Management Institute (IWMI) investigated 524 paddy soils in Thailand and found that Cd concentrations were 0.5-284 mg/kg (Simmons et al 2005). Kosolsaksakul et al (2014) stated that paddy fields were severely contaminated by zinc ore extraction in the Mae Tao watershed of northwest Thailand, and Cd contents there ranged from 2.5-87.6 mg/kg.…”
Section: Anthropogenic Pollution Sources Analysismentioning
confidence: 99%
“…The cadmium contamination was reported in rice, soil and sediment in around Mae Tao Stream, the main source of water supply for agriculture, which is located at Mae Sot District, Tak Province in the north of Thailand [1], [2]. Mae Tao Stream passes through a zinc rich area where the zinc mining has been actively operated for more than 30 years.…”
Section: Introductionmentioning
confidence: 99%